PENGARUH PENGAWASAN INTERNAL, PEMAHAMAN SISTEM AKUNTANSI KEUANGAN, DAN KAPASITAS SUMBER DAYA MANUSIA TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH PADA SKPD PEMERINTAH KOTA MANADO - Ponamon, Irene Fransisca (Universitas Sam Ratulangi, 2014)
The research was conducted on the basis of the results of Local Government Finance Report that the financial statements of Manado City Government has not met the criteria as requirements quality financial statements. This is evidenced by the opinion received by the Manado City Government during 2008 to 2012 as, Qualified Opinion, Adverse Opinion, Disclaimer Opinion, Adverse Opinion , and Qualified Opinion. Adverse and Disclaimer Opinions received by the city of Manado may raise questions for society about possible irregularities have occurred many budgets.This study aims to determine the influence of internal controls, an understanding of financial accounting systems, and human resources capacityÂ to quality of government financial reporting informationÂ atÂ SKPD in Manado city government. The results of the study were statistically conclude that internal control, understanding financial accounting, and human resource capacity jointly affect the quality of government financial reporting information at SKPD in Manado city, however partially, the human resource capacity has no effect to quality of government financial reporting information at SKPD in Manado City. Suggestions from this study is Manado City Government is expected to improve qualifications in the field of education, namely the employees who receive educational background in accounting.